Primary Prophylaxis With Biosimilar Filgrastim for Patients at Intermediate Risk for Febrile Neutropenia: A Cost-Effectiveness Analysis. Issue 8 (August 2021) - Li, Edward; Mezzio, Dylan J.; Campbell, David; Campbell, Kim; Lyman, Gary H.
Abstract : PURPOSE: Temporary COVID-19 guideline recommendations have recently been issued to expand the use of colony-stimulating factors in patients with cancer with intermediate to high risk for febrile neutropenia (FN). We evaluated the cost-effectiveness of primary prophylaxis (PP) with biosimilar filgrastim-sndz in patients with intermediate risk of FN compared with secondary prophylaxis (SP) over three different cancer types. METHODS: A Markov decision analytic model was constructed from the US payer perspective over a lifetime horizon to evaluate PP versus SP in patients with breast cancer, non–small-cell lung cancer (NSCLC), and non-Hodgkin lymphoma (NHL). Cost-effectiveness was evaluated over a range of willingness-to-pay thresholds for incremental cost per FN avoided, life year gained, and quality-adjusted life year (QALY) gained. Sensitivity analyses evaluated uncertainty. RESULTS: Compared with SP, PP provided an additional 0.102-0.144 LYs and 0.065-0.130 QALYs. The incremental cost-effectiveness ranged from 5, 660 in US dollars (USD) to 20, 806 USD per FN event avoided, 5, 123 to 31, 077 USD per life year gained, and 7, 213 to 35, 563 USD per QALY gained. Over 1, 000 iterations, there were 73.6%, 99.4%, and 91.8% probabilities that PP was cost-effective at a willingness to pay of 50, 000 USD per QALY gained for breast cancer, NSCLC, and NHL, respectively. CONCLUSION: PP with a biosimilar filgrastim (specifically filgrastim-sndz) is cost-effective in patients with intermediate risk for FN receiving curative chemotherapy regimens for breast cancer, NSCLC, and NHL. Expanding the use of colony-stimulating factors for patients may be valuable in reducing unnecessary health care visits for patients with cancer at risk of complications because of COVID-19 and should be considered for the indefinite future.